Some Historical Conceptual, Social and Musical Aspects of the Lullaby Song - Castro, Isabel (2013)
The fact of finding in some places of the world references to lullabies leads me to meditate on its value and action on early childhood. Maternal care, implying a set of several attitudes and feelings, universaly possesses very own moments, almost unique, of contact between the mother and her baby. Thus, singing lullabies falls on the uniqueness of these moments that enable the establishment of the connection between mother and child. In this article I will focus on the study of lullaby addressing both its antiquity and diffusion among different cultures, and some of the features that make it a unique musical genre with specific purposes.Keywords: ;; ;;